ENDOCRINE VIRTUAL CLINIC PATIENT SATISFACTION: A SINGLE-CENTRE EXPERIENCE IN PAHANG, MALAYSIA DURING THE CORONAVIRUS-19 (COVID-19) PANDEMIC - Keong, See Chee; Veerasamy, Hema Lata; Binti Mohd Samsudin, Mimi Syafiqah; Binti Shamsudin, Norhaslinda; Binti Ramli, Nur Azwani; Bt Che Derahman, Lizawati; Peng, Eng Wei (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The COVID-19 pandemic had placed significant strain on the health care system across the world. The implementation of virtual clinics was suggested as an option to reduce face-to-face outpatient appointments and clinic congestion. This study highlights the challenges and patient satisfaction regarding the implementation of a Hyperthyroidism and Hypothyroidism Virtual Clinic in Hospital Sultan Haji Ahmad Shah, Temerloh, Pahang, Malaysia. METHODOLOGY This is a cross-sectional study that included all patients who received virtual clinic appointments between October 2020 and May 2021. Patients’ satisfaction with their virtual clinic appointments was assessed by nurses through phone interviews. Patients’ demographic data and responses to treatment were obtained through electronic medical data. RESULTS Ninety-five patients were included in the study. The patients involved had a mean age of 38.9 (SD 13.6) years, 73.7% were female, and 87.4% were of Malay ethnicity. 65.3% of virtual clinic patients had hyperthyroidism. The mean free T4 for hypothyroid and hyperthyroid virtual clinic patients were 20.9 (SD 9.3) pmol/L and 21.7 (SD 11.9) pmol/L, respectively. The mean TSH for hypothyroid virtual clinic patients was 7.3 (SD10.5) mU/L. Nearly 50% of patients had no medication dose changes during their follow-up, while 26.3% required incremental adjustment of medication doses. 88.4% of patients were satisfied with their virtual clinic sessions. 66.3% of the patients interviewed preferred virtual clinics due to reduced waiting time for consultation, while 48.4% mentioned the decreased need for multiple and long hospital visits for clinical consultation. The main negative views cited regarding the virtual clinics were patients’ poor internet connection and medication collection issues. CONCLUSION This study demonstrated that patients were receptive to the virtual clinic concept. Patient consultations were focused and waiting time was greatly reduced. Adjustments to patient medications also could be done effectively in a virtual clinic setting.